Infodemic and the Crisis of Distinguishing Disinformation from Accurate Information: Case Study on the Use of Facebook in Kosovo during COVID-19 - Qerimi, Gëzim; Gërguri, Dren (Information & Media, 2022)
Social media over the years has been shown to be an important source for information in times of crisis and confusion. Citizens who were restricted to their homes due to pandemic-mitigating lockdowns have desired more than ever to be informed about the pandemic, have been exposed to a host of misinformation, which has also affected their trust in the media, as well as the way they have been informed about COVID-19 in the days following. This research aims to analyze how citizens have used the media during COVID-19 and whether they were capable to accurately distinguish misinformation or disinformation from accurate information. To respond to the research question and to test hypotheses a survey based on purposive sampling method was used with citizens that included 850 respondents from the seven main regions of Kosovo. Results of this study indicate that the information-seeking habits have changed within a short period of time and Kosovo society can easily be affected by disinformation. The data demonstrated that citizens failed to distinguish between false and true news. The results also highlight that education and economic situation were significant indicators, with less educated people, and people with the weakest economic well-being are more likely to believe false information.
Keywords: Audience; COVID-19; Disinformation; Infodemic; Media